Grain Sorghum Cost-Return Budget in Northeast Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2002)
This publication projects a budget that reflects expected income and costs based on grain sorghum production in northeastern Kansas.
MF573_2002_10
Keywords: MF573; Economics; Crops; MF